Banana fertigation with treated sanitary wastewater: postharvest and microbiological quality - Pablo Fernando Santos Alves (Semina: Ciências Agrárias, 2017)
Sewage may serve as a source of water and nutrients for plants. In this study, the effects of fertigation with treated sanitary wastewater from Janaúba Sewage Treatment Plant were evaluated on the postharvest and microbiological quality of ‘Prata-Anã’ banana. A randomized block experimental design was used. Four concentrations of wastewater were tested (70, 130, 170, and 200% of 150 kg ha-1 sodium). A wastewater-free control treatment was used for comparison. Two crop cycles were assessed for postharvest and microbiological quality. The parameters measured included total soluble solids, titratable acidity, total soluble solids/titratable acidity ratio, pH, total coliforms, and fecal coliforms on both the peel and the pulp. In the first crop cycle, both soluble solids and fruit pulp pH decreased as wastewater level increased up to a maximum of 141.5%. These correlations were not observed in the second cycle. Wastewater management did not affect the titratable acidity of the soluble solids. The agricultural application of treated sanitary wastewater provided banana fruits with a microbiological profile similar to that obtained with the control (pure water) and with mineral fertilizers. A microbial balance is necessary to maintain the nutritional status of the banana crop.